CDK7 Inhibitor THZ1 Induces the Cell Apoptosis of B-Cell Acute Lymphocytic Leukemia by Perturbing Cellular Metabolism - Abudureheman, Tuersunayi; Xia, Jing; Li, Ming-Hao; Zhou, Hang; Zheng, Wei-Wei; Zhou, Neng; Shi, Rong-Yi; Zhu, Jian-Min; Yang, Li-Ting; Chen, Li; Zheng, Liang; Xue, Kai; et al. (Frontiers in Oncology, 2021)
B-cell acute lymphocytic leukemia (B-ALL) is a malignant blood cancer that develops in children and adults and leads to high mortality. THZ1, a covalent cyclin-dependent kinase 7 (CDK7) inhibitor, shows anti-tumor effects in various cancers by inhibiting cell proliferation and inducing apoptosis. However, whether THZ1 has an inhibitory effect on B-ALL cells and the underlying mechanism remains obscure. In this study, we showed that THZ1 arrested the cell cycle of B-ALL cells in vitro in a low concentration, while inducing the apoptosis of B-ALL cells in vitro in a high concentration by activating the apoptotic pathways. In addition, RNA-SEQ results revealed that THZ1 disrupted the cellular metabolic pathways of B-ALL cells. Moreover, THZ1 suppressed the cellular metabolism and blocked the production of cellular metabolic intermediates in B-ALL cells. Mechanistically, THZ1 inhibited the cellular metabolism of B-ALL by downregulating the expression of c-MYC-mediated metabolic enzymes. However, THZ1 treatment enhanced cell apoptosis in over-expressed c-MYC B-ALL cells, which was involved in the upregulation of p53 expression. Collectively, our data demonstrated that CDK7 inhibitor THZ1 induced the apoptosis of B-ALL cells by perturbing c-MYC-mediated cellular metabolism, thereby providing a novel treatment option for B-ALL.